Sistem E-Antre dalam Pelayanan Publik Serta Relevansinya dalam Pencegahan Korupsi (Studi pada DISDUKCAPIL Kota Banda Aceh) - Muhammad Ihsan (Komisi Pemberantasan Korupsi, 2021)
Corruption in public service sector has a simple pattern yet it occurs massively. The Department of Population and Civil Registration (Disdukcapil) is no exception. Despite implementing the e-queuing system, corruption can still be found. This study aims to describe the implementation of the e-queuing system and to figure out the form and model of its socialization by highlighting the optimization of the e-queue system, the effectiveness socialization and its relevance to the corruption prevention efforts. This study employs a socio-legal approach with juridical empirical method and the data was collected through documentation and interview. The results show that: 1) the implementation of e-queuing system needs to be optimized; 2) e-queuing system has yet to be effectively socialized; 3) e-queuing system is very relevant to the corruption prevention efforts due to its ability to limit the public’s direct contact and the efficient use of time. Thus, preventing the use of services from a third party.